Optimización del desempeño financiero por medio de gestión de riesgos, aplicación de la norma BS ISO 31000:2018 para pequeñas y medianas empresas (Pymes) CASO KPITAL NETWORKS SAS. (2025)
Financial risk management must be an essential part of the culture organizational structure of small and medium-sized enterprises (SMEs), regardless of their size or sector, this is not an exclusive approach of large corporations, since each company, by carrying out its corporate purpose, generating jobs and participating in a market, has the responsibility of guaranteeing its viability and financial health